(untitled) (Clinics, 2023)
Background & Aims: Perianal fistulizing Crohn's disease is the main risk factor for anal cancer in patients with inflammatory bowel disease. Whether this occurs due to a higher frequency of human papillomavirus remains unclear. The authors aimed to evaluate the prevalence of HPV and high-risk HPV in patients with perianal Crohn's disease, compared with a control group. Methods: The authors conducted a two-center cross-sectional study in which perianal fistulizing Crohn's disease patients were matched for age and sex with patients with anorectal fistula without Crohn's disease. Biopsy specimens were obtained from fistulous tracts during examination under anesthesia for both groups. The samples were sent for HPV detection and genotyping using the INNO-LiPA test. Results: A total of 108 subjects (54 in each group) were recruited. The perianal fistulizing Crohn's disease group showed a statistically higher frequency of HPV in the fistulous tract than the control group (33.3% vs. 16.7%; p = 0.046). Separate analyses on high-risk types demonstrated that there was a numerically higher frequency of HPV in the perianal fistulizing Crohn's disease group. In multiple logistic regression, patients with perianal fistulizing Crohn's disease were found to have a chance of HPV 3.29 times higher than patients without Crohn's disease (OR = 3.29; 95% CI 1.20‒9.01), regardless of other variables. The types most frequently identified in the perianal fistulizing Crohn's disease group were HPV 11 (12.96%) and HPV 16 (9.26%). Conclusion: Perianal fistulizing Crohn's disease is associated with a higher prevalence of HPV than in patients with anorectal fistula without Crohn's disease.